EARLY POST-OPERATIVE PERINEAL WOUND COMPLICATIONS IN PATIENTS UNDERGOING EXTRA LEVATOR ABDOMINOPERINEAL EXCISION, A RETROSPECTIVE STUDY AT DEPARTMENT OF SURGICAL ONCOLOGY - Jamal, Aun; Batool, Sadaf; Haq, Ihtisham Ul; Mohsin, Jibran; Shakeel, Osama; Khattak, Shahid; Syed, Aamir Ali (Pakistan Armed Forces Medical Journal, 2020)
Objective: To emphasize on the early wound complications of the above-mentioned procedure. Study Design: Retrospective observational study. Place and Duration of Study: The study was conducted at department of Surgical Oncology, Shaukat Khanum Memorial Cancer Hospital & Research Center, from Jan 2014 to Dec 2019. Methodology: A total of 84 patients were included in the study who underwent extra levator abdominoperineal excision. It was a retrospective study with convenient sampling. The data was retrieved from Hospital information system (HIS) that is a fully electrotonic system and is prospectively maintained. Variables were expressed as median and IQR was calculated. Univariate and multivariate analysis was performed. The p-value of ≤0.05 was considered significant. Results: Wound infection was observed in 32 (38.09%) of the patients. Wound dehiscence was seen is 5 (5.95%) of the patients. Median day of detection of infection was day 10 (5-22). Median hospital stay was 7 (4-22) days. On multivariate analysis the correlation of Body mass index with perineal wound infection was statistically significant with p-value of 0.045. Conclusion: Extra levator abdominoperineal excision is a procedure with significant perineal wound complication rate. The occurrence of perineal wound complications is multifactorial. Judicial use of the procedure is warranted.